Modeling of interspecies electron transfer in anaerobic microbial communities. (February 2021) - Desmond-Le Quéméner, Elie; Moscoviz, Roman; Bernet, Nicolas; Marcus, Andrew
Graphical abstract: Highlights: Redox mediators with various potentials change energy distribution between microbes. Bioelectrochemical equations and concepts are currently being used for IET modeling. Models confirm the potential of DIET to improve electron transfer rates. Fundamental knowledge on the characteristics of IET is needed for adequate modeling. Abstract : Interspecies electron transfer (IET) is a key phenomenon in anaerobic ecosystems, which is traditionally modeled as hydrogen transfer. Recently discovered alternative mediated IET (MIET) or direct IET (DIET) offer exciting alternative mechanisms of microbial partnerships that could lead to new strategies for the improvement of biotechnologies. Here, we analyze mathematical modeling of DIET and MIET in anaerobic ecosystems. Bioenergetics approaches already enable the evaluation of different energy sharing scenarios between microorganisms and give interesting clues on redox mediators and on possible ways of driving microbial communities relying on IET. The modeling of DIET kinetics however is currently only in its infancy. Recent concepts introduced for the modeling of electroactive biofilms should be further exploited. Recent modeling examples confirms the potential of DIET to increase the IET rates compared to H2 -MIET, but also point out the need for additional characterizations of biological components supporting IET to improve predictions.